2020
DOI: 10.1007/s42979-020-00354-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Thin-Walled Approximation to Evaluate Properties of Complex Steel Sections Using C++

Abstract: Steel sections have several applications in the construction industry. They are often used in the design and construction of huge industrial complexes. They also are used in transport, shipbuilding and packaging industries. Typical steel sections are used, and their properties have been recorded and are not needed to be calculated per application. They are recorded in most design software and used easily when required. This work focusses on using thin-walled approximation to calculate the section properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…The area enclosed between the ascending and descending curve is called the hysteresis loop. The area of the hysteresis loop can be used to judge the mechanical stability of structured systems: the smaller it is, the more mechanically stable the system is [28,45].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area enclosed between the ascending and descending curve is called the hysteresis loop. The area of the hysteresis loop can be used to judge the mechanical stability of structured systems: the smaller it is, the more mechanically stable the system is [28,45].…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of this work is related to our development -an ointment composition -which is a combined agent with antimicrobial properties (due to the content of nanosilver) and regenerative properties (due to the content of highly dispersed Zinc oxide). Zinc oxide, being a source of the essential trace element Zinc, locally affects the skin area, releasing Zinc ions that saturate damaged tissues and promote accelerated regeneration of damaged skin [11,[22][23][24][25][26][27][28][29]. The ointment composition well moisturizes the damaged skin with the simultaneous restoration of the epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…CDC recommendations are optional, and therefore may not be universally applied in different MPP facilities [ 12 ]. In addition, there are no CDC guidelines on additional and novel measures that are specific for food processing contexts [ 23 ] as current CDC guidelines appear to be drawn from the general knowledge of what is understood about infectious diseases, rather than specific guidelines based on AVT in an MPP context. For example, hand hygiene is the most effective way to prevent the spread of infectious diseases generally, yet the availability of this measure only offers limited protection from viruses such as COVID-19 that are spread by respiratory droplets [ 24 ].…”
Section: An Airborne Virus Model Of Food Safetymentioning
confidence: 99%
“…There are works on the study of the venom activity of migalamorphic spiders [21], which concluded that the polypeptide combinations of the studied poisons have strong antiviral activity. The effect of other biologically active substances on antiviral activity has also been studied [22][23][24][25][26][27][28][29][30]. It is also worth noting the development of digitalization technologies [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%